An Assessment On Madrasa Design As Symbol Of Communal Value Using Semiotic Analysis – Case Study of Rustem Pasha Madrasa (Sains Humanika, 2018)
The purpose of this paper is to propose an appropriate design solution for madrasa as a center of communal values development. This paper is vital as there are many arising issues relating to madrasa development in the present context that requires much needed attention from various parties. This is because the madrasa's utilitarian function and existence as a community center began to change once transformation occurred to civil society. This factor happened due to modernization and Western influence in the context of Islamic propagation. Past literature on madrasa development focused more on limited areas of study such as the documentation of historical ownership, management and maintenance, learning curriculum, discussion on the role of women in madrasa education, and the construction process of the madrasas. To date, none discusses on the strategies how to design the madrasa to function as a community center. This research analyses historic prominent madrasa Rustem Pasha (1547-1550) designed by the great architect Sinan during the expansion period of Ottoman empire (1453-1566) based on literature review using semiotic approach to establish the appropriate design attributes that interrelated with communal values. Findings indicate that five communal values involving transparency, propriety, modesty, gratitude and obligation are embedded in this historic madrasa built form and spatial arrangement for centuries as a form of ‘sign’ to convey message to the user. This established reference design approaches from this research is of benefit for designers, builders, developers and relevant authorities to build a communal type madrasa in the future.
Keywords: Madrasa; communal values; sign; semiotic; architecture